Exploration of the mechanism of Polyphyllin I against hepatocellular carcinoma based on network pharmacology, molecular docking and experimental validation - Yilong Chen; Qiuying Wang; Shuixiu Bian; Jing Dong; Jie Xiong; Jiamei Le (Discover Oncology)
Abstract Purpose Hepatocellular carcinoma (HCC) is a leading cause of cancer-related death worldwide. Targeted therapies hold promise for HCC treatment, and understanding the molecular mechanisms of action is crucial for developing novel therapeutic strategies. Polyphyllin I, a natural compound with known antitumor activity, represents a potential therapeutic candidate. Methods This study employed a network pharmacology approach to investigate the anti-HCC effects of Polyphyllin I and its underlying mechanisms. Drug and disease related targets were identified and intersected to construct Components-Gene Symbols-Disease and Protein–Protein Interaction networks. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses were performed. Molecular docking simulations were conducted to explore the interactions between Polyphyllin I and key pathway proteins (VEGF-C and β-catenin). Finally, in vitro and in vivo experiments validated the anti-HCC effects and underlying mechanisms of Polyphyllin I. Results Network pharmacology analysis revealed that Polyphyllin I targets multiple genes and pathways implicated in HCC development and progression. GO and KEGG analyses identified significant enrichment of pathways related to cell proliferation, apoptosis and angiogenesis, including VEGF and the Wnt/β-catenin signaling pathways. Molecular docking simulations demonstrated strong binding affinities between Polyphyllin I and VEGF-C and β-catenin. In vitro and in vivo experiments confirmed that Polyphyllin I effectively inhibits HCC cell proliferation, induces apoptosis, and suppresses angiogenesis, potentially by modulating the VEGF-C and Wnt/β-catenin signaling pathways. Conclusions The study provides compelling evidence for the antitumor activity of Polyphyllin I in HCC and elucidates its possible molecular mechanisms, suggesting that Polyphyllin I holds great potential as a therapeutic agent for HCC.